Sexually Transmitted Infections in Bangladesh: A Narrative Synthesis of Multidimensional Impact (Journal of Rangpur Medical College, 2026)
Background: Sexually transmitted infections (STIs) remain a global public health challenge, especially in low- and middle-income countries where social, economic, and structural factors increase vulnerability. Objective: The objective of this narrative review was to synthesize evidence on the epidemiology, determinants, multidimensional impacts, and prevention strategies of sexually transmitted infections (STIs) in Bangladesh. Methods: A narrative literature review of studies published from 2000 to 2024 was conducted using PubMed, ScienceDirect, and Google Scholar. Ten studies met inclusion criteria. Data were analyzed using qualitative content analysis, categorizing themes into epidemiology, determinants, impacts, and control strategies. Results: HIV appeared in 20% of studies, mostly among people who inject drugs, while 60% reported high prevalence of other STIs among female sex workers. Structural determinants such as poverty and inequality were identified in 30% of studies, and behavioural factors such as low condom use in 20%. Health complications (60%), social stigma (20%), and gender-related vulnerability (20%) were documented. Prevention strategies were discussed in 70% of studies, but were mostly population-specific rather than integrated. Conclusion: STIs in Bangladesh are influenced by behavioural, social, and structural determinants. Integrated, inclusive, and evidence-based interventions addressing both individual and societal risk factors are necessary to prevent future escalation.J Rang Med Col.2026 Mar;11(1): 213-220